Characterization of the floral structure and evaluation of seeds production from different materials of Tithonia diversifolia Hemsl.) A. Gray. in Cuba - Rodríguez, Idalmis; Padilla, C.; Medina, Yolaine (Cuban Journal of Agricultural Science, 2021)
In order to characterize the reproductive structure, the production and seed germination of different materials of Tithonia diversifolia Hemsl.) A. Gray, a total of three experiments were performed at different times and five plant materials were evaluated (3, 10, 16, 23, 25). The harvest of ten heads (2018 and 2019) was carried out by means of a random sampling at five points on the diagonal of the field. The evaluated materials constitute the treatments. A completely random design was used for the analysis of the variables diameter (cm) and seed heads weight (g), number and weight (mg) of full and empty seeds and of PGS seed heads-1. To the total number and the germination percentage of seed at different times 3, 5, 7 and 30 days) a simple classification nonparametric analysis of variance was performed. The studied materials showed phenotypic differences in terms of their reproductive structure. The seed heads of material 25 had a higher diameter. Material 16, due to its higher weight, distinguished itself from the rest of the evaluated materials. The waste from the seed heads is approximately 71.18 % of their total weight. The seed production of materials 10, 23 and 25 is very similar with respect to the total number of seeds in the seed heads, as well as the number of empty seeds. However, material 23 showed a lower number of full seeds (P ≤ 0.0005). These results contribute to the knowledge of the reproductive characteristics of each specific material, which will allow the development of future studies related to the gamic seed production strategy. Key words: gamic seed, Tithonia, germination, inflorescences.